The Implication of ICT on Business Education - Kumar, Sanjeev; Pallathadka, Harikumar; Pallathadka, Laxmi Kirana (Integrated Journal for Research in Arts and Humanities, 2022)
This article outlines the significant difficulties and delivers a glimpse into the future of education and ICT. In the introduction, we learn about the so-called "knowledge-based society" and how technological advancements have opened the way for educational progress and spurred the creation of new data. The article tends to discuss the significance of Involvement in the modification of the teaching-learning process by each educational agent (student/teacher). This research over the impact of ICT in education is focused on the doctrinal methodology. It makes use of several research articles from books and journals to formulate the final opinion. The analysis conducted by the researcher prominently makes use of primary sources of information. The teaching and learning processes in Business Education at higher institutions in several countries, including India, are still primitive. Due to the widespread lack of enthusiasm for innovation, both professors and students continue to rely on textbook knowledge and lecturer-led class verbalization. Both academics and students believe that the administration has ignored education. As a result, many Business Education teachers and students have not yet wholly embraced ICT for teaching and learning. As a result, we are soliciting research in this area. Incorporating ICT into education can aid in developing a new model of learning and teaching in a world reduced to a small village by technology. Every industry and government has been transformed by the widespread use of information and communication technology (ICT) over the past two decades.